The Effect of Fluid Management Application on Hemodialysis Patients with Excess Fluid - Damanik, Candra Meriani; Putra, Imam Budi; Siregar, Cholina Trisa; Saidah Nst, Siti (Universitas Aisyah Pringsewu, 2020)
Renal disease is a disorder that occurs in the kidneys. Such diseases caused by various factors, such as infections, tumours, congenital disorders, metabolic or degenerative diseases, and others. Chronic renal disease usually occurs slowly and is chronic. Patients suffering from chronic renal disease require renal replacement therapy (TPG) to maintain their life. The success of this chronic renal disease therapy depends on the patient's involvement in maintaining their diet and fluids. Fluid management experienced by hemodialysis patients is essential to decrease the risk of excess fluid and is a significant factor that can determine the success of hemodialysis therapy. This research was performed aiming to analyze the effect of implementing fluid management on the excess fluid in hemodialysis patients. This study employed a quasi-experimental design through pre-test and post-test methods using a control group. There were 90 respondents involved in this research as samples, who were divided into two groups, 45 respondents in the intervention group and another 45 respondents in the control groups. These samples were selected through purposive sampling. Furthermore, the research data were collected using fluid management guide instruments, fluid intake monitoring charts, and weight recording sheets. The results revealed that there was no effect of fluid management on IDWG values between the intervention group after fluid management and the control group of hemodialysis patients (t = -1.58; p = 0.118). The results of this study can recommend that the application of fluid management with family support can be an action to decrease excess fluid in hemodialysis patients.Abstrak: Penyakit Ginjal merupakan kelainan yang mengenai organ Ginjal. Penyakit ini timbul akibat berbagai faktor, misalnya infeksi, tumor, kelainan bawaan, penyakit metabolik atau degeneratif, dan lain-lain. Penyakit Ginjal kronik, biasanya timbul secara perlahan dan sifatnya menahun. Pasien dengan penyakit ginjal kronik membutuhkan terapi pengganti ginjal (TPG) untuk mempertahankan hidup. Keberhasilan terapi penyakit ginjal kronik sangat bergantung pada keterlibatan pasien dalam menjaga diet dan cairan. Manajemen cairan pada pasien hemodialisa sangat penting guna mengurangi resiko kelebihan cairan dan merupakan faktor penting yang dapat menentukan keberhasilan terapi hemodialisa. Tujuan dari penelitian ini adalah menganalisa pengaruh penerapan manajemen cairan terhadap kelebihan cairan pada pasien hemodialisa. Penelitian ini menggunakan desain quasi experiment dengan metode pre test dan post test with kontrol group. Sampel penelitian ini adalah 90 responden yang dibagi dalam dua kelompok, 45 kelompok intervensi dan 45 kelompok kontrol. Teknik pengambilan sampel penelitian ini menggunakan purposive sampling. Pengumpulan data penelitian menggunakan instrumen panduan manajemen cairan, chart pemantauan intake output cairan, lembar pencatatan berat badan. Hasil penelitian menunjukkan bahwa tidak ada pengaruh manajemen cairan terhadap nilai IDWG antara kelompok intervensi setelah manajemen cairan dengan kelompok kontrol pasien hemodialisa (t = -1.58; p = 0.118).